Between care, work, and education: what remains for women beneficiaries of the Bolsa Família Program (PBF) (Práxis Educativa, 2025)
This article discusses the trajectories of work, schooling, and life of women beneficiaries/heads of the Bolsa Família Program (PBF) [Brazilian Cash Transfer Program] and how they are shaped by the program’s conditionalities, configuring what we call a pater-politics [a patriarchal form of politics]. As a method, we used Marx’s (2017) historical materialism—dialectical, historical, and social movement, and, in its specificity, capitalist—expressed in social policies. The field research was based on extensive documentary analysis, as well as on records from the Social Assistance Reference Centers (CRAS, acronym in Portuguese) – 564 files – and on interviews with 18 Family Reference women, resulting in five categories, one of which addresses the relationship between care, work, and education, and how these women are affected and shaped by these three dimensions. It was concluded that they are used as a means to ensure compliance with conditionalities and the success of the program, while being excluded from other dimensions of life, with their practices devalued as non-work and, ultimately, disregarded as political subjects.Keywords: Women, patriarchy and capital. Work, education and social policy. PBF, pater-policy and care.